Impact Assessment of Video-based Information Dissemination in Agriculture: A Case of Digital Green Initiative (Indian Journal of Extension Education, 2015)
Digital Information and Media are excellent tools to upsurge knowledge which is an important production factor in agriculture. The generic term used for the Digital Information Sector in agriculture is ICT (Information and Communication Technologies). ICTs contribute to the display, processing, storing and spread of information through electronic means by using several tools like mobile, internet, kiosks, audio, and video etc. There are number of ICT projects in India which uses different ICT tools for dissemination of information and knowledge. The effectiveness and efficiency of all these tools varies with the situation. This study was conducted to know the effectiveness of the digital video which was used by Digital Green, in dissemination of information. The study was conducted in the district of Andhra Pradesh and Madhya Pradesh. An ex-post facto research design was used for the study purpose. The data was collected from the 80 beneficiary farmers from both the states and 40 farmers from the control village in the respective states. The parametric test, i.e. t-test was used to compare the production of crops and change in income of the farmers before and after the intervention of the Digital Green services. A significant difference was found for the entire grown crop and also in the incomes of the beneficiary and control farmers.